Monitoring and Evaluating Mozambique’s Poverty Reduction Strategy PARPA 2006-2008. A Synopsis of Three Qualitative Studies on Rural and Urban Poverty. - Tvedten, Inge; Rosário, Carmeliza; Paulo, Margarida (Chr. Michelsen Institute, 2009)
The purpose of this synopsis is to facilitate discussions between the government, civil society organisations, donors and other stakeholders in Mozambique’s efforts to reduce poverty and, more specifically, to contribute to the Impact Assessment Report (Relatótio de Avaliação de Impacto, RAI) which is to be carried out in 2009. We will focus on our main findings and preliminary conclusions, and will to the extent possible avoid repeating data found in the original reports to ease accessibility. The discussions related the synopsis will also be used to further identify the most relevant topics and approaches for the final three studies, in order to secure their maximum utility for the government’s monitoring and evaluation programme. The synopsis will be divided into six parts following this Introduction. In Chapter 2 we briefly account for the analytical framework and methodological approaches of the studies. In Chapter 3 we present what we have identified as aspects of Mozambique’s political economy with particular impacts on the situation in local communities. In Chapter 4 we analyse the main features of the political context at the level of districts through which poverty reduction is implemented. In Chapter 5 we present the main findings from the adapted surveys we have carried out, with a focus on the similarities and differences between the three areas of study. In Chapter 6 we assess the outcome of our qualitative and participatory approaches to our analyses. And finally, in Chapter 7, we present preliminary conclusions and recommendations from the first three studies and outline the approach of the three follow-up studies.
E-version: ISBN 978-82-8062-340-9
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

"Xiculungo" - Social relations of urban poverty in Maputo, Mozambique - Paulo, Margarida; Rosário, Carmeliza; Tvedten, Inge; Chr. Michelsen Institute (Chr. Michelsen Institute (CMI), 2007)
This is the second in a series of six participatory and qualitative studies of poverty in Mozambique, done with the objective of supporting the government in monitoring and evaluating the ongoing Action Plan for the Reduction of Absolute Poverty, PARPA II (GdM 2005). The first report looked into social relations of rural poverty in northern Mozambique, with special reference to the District of Murrupula in the Nampula province (Tvedten, Paulo and Rosário 2006). This report will analyse social relations of urban poverty, with special reference to four settlement areas (bairros) in Mozambique’s capital Maputo (see Terms of Reference, Annex 1). The Government of Mozambique and donors have invested considerable effort and resources in economic development and the reduction of poverty. While this has led to improvements in terms of an economic growth of 8 percent per annum over the past ten years (Arndt et al. 2006) and a reduction in the proportion of Mozambicans living in poverty from 69 to 54 percent (INE 2004), key socio-economic indicators are still very serious: GDP per capita is USD 1,117, the adult literacy rate is 46.5 percent, and life expectancy at birth is 41.9 years (World Bank 2006; UNICEF 2007). This places Mozambique at number 172 of 177 countries in UNDP’s Human Development Index, which makes it the least developed country in Southern Africa (UNDP 2007). Research-based information about poverty is recognised as important for Mozambique’s poverty reduction strategies, as these are expressed in the Government’s Five Year Plan (GoM 2005) and the related PARPA II (GdM 2005). Key data for the monitoring and evaluation of poverty in Mozambique stem from the National Census (INE 1997 and forthcoming 2008), the National Household Survey IAF (INE 1997 and 2004) and the National Demographic and Health Survey (MdS 2005), as well as a number of analyses by the Government of Mozambique based on these data (see e.g. DNPO 2004; Chiconela 2004; Maximiano et al. 2005). In addition, international organisations have commissioned several studies on their own, of which those undertaken by UNDP (2006), UNICEF (2007) and the World Bank (2007) are the most recent and comprehensive
OCLC: 874829175
Keywords: G - Mozambique / Moçambique; Important; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
ISSN 0805-505X ISBN 82-8062-172-5
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização